Health inequalities and income for people with spinal cord injury. A comparison between and within countries. (September 2021) - Oña, Ana; Strøm, Vegard; Lee, Bum-Suk; Le Fort, Marc; Middleton, James; Gutenbrunner, Christoph; Pacheco Barzallo, Diana
Abstract: Income and health are related in a bi-directional manner, whereby level of income affects health and vice versa. People in poorer households tend to experience worse health status and higher mortality rates than people in wealthier households, and, at the same time, having poor health could restrict workability leading to less income. This gap exists in almost every country, and it is more pronounced in more unequal countries and in vulnerable populations, such as people experiencing disability. The goal of this paper is to estimate the health-income gap in people with a Spinal Cord Injury (SCI), which is a chronic health condition often associated with multiple comorbidities that leads to disability. As data on mortality is inexistent, to estimate the health-income gap for persons with SCI, this paper uses two health outcomes: the number of years a person has lived with the injury, and a comorbidity index. Data was obtained from the International Spinal Cord Injury survey (InSCI), which is the first worldwide survey on community-dwelling persons with SCI. To compare across countries, the health outcomes were adjusted through hierarchical models, accounting for country fixed-effects, individual characteristics such as age and gender, and injury characteristics (cause, type and degree). Our results suggest that for the years living with SCI, the gap varies from 1 to 6 years between the lowest and the highest income groups. The main driver of such a difference is the cause of injury, where injuries caused by work accidents showed the biggest gap. Similarly, for the comorbidity index, persons with SCI in poorer deciles reported significantly more comorbidities, forty times more, than people in richer deciles. Highlights: Income is highly associated with health disparities in people living with long-term disabilities. This is the first analysis of the health-income gap using the International Spinal Cord Injury survey (InSCI). People with SCI in poorer income groups report more comorbidities and live fewer years after the injury. Work accidents are the main driver of the inequality.